Anesthesia for Cesarean Section: Retrospective Comparative Study - Al-Husban,Naser; Elmuhtaseb,Mohammad Sami; Al-Husban,Hedaieh; Nabhan,Mohammed; Abuhalaweh,Hamza; Alkhatib,Yasmine Mohamed; Yousef,Maysa; Aloran,Bayan; Elyyan,Yousef; Alghazo,Asma (International Journal of Women's Health, 2021)
Naser Al-Husban,1 Mohammad Sami Elmuhtaseb,1 Hedaieh Al-Husban,2 Mohammed Nabhan,3 Hamza Abuhalaweh,3 Yasmine Mohamed Alkhatib,3 Maysa Yousef,3 Bayan Aloran,3 Yousef Elyyan,3 Asma Alghazo3 1Faculty of Medicine, The University of Jordan, Amman, Jordan; 2Al-Noor Fertility Center, Eye Specialty Hospital, Amman, Jordan; 3Obstetrics and Gynecology Department, Jordan University Hospital, Amman, JordanCorrespondence: Naser Al-HusbanFaculty of Medicine, The University of Jordan, P O Box 2194, Amman, 11941, JordanTel +962-772086080Fax +96264643217Email Husban48@yahoo.comBackground: Cesarean section is a widely performed surgery.Objective: To compare anesthetic types regarding feto-maternal outcomes.Materials and Methods: Retrospective comparative study of 3599 cesarean sections (emergency and elective categories).Results: Mean APGAR score was statistically higher in the spinal than general anesthesia among the emergency category, P = 0.000 and 0.026, respectively, with no significant difference in the elective category. Estimated blood loss among the elective category was statistically significantly higher in the spinal than general anesthesia, P = 0.001. However, among the emergency category, it was significantly higher in the general than in spinal or epidural anesthesia, P = 0.000. Diclofenac sodium was used more after spinal than general anesthesia (P = 0.000), with no significant difference between epidural and general or between epidural and spinal anesthesia. Pethidine hydrochloride (HCL) was used more after general than after spinal anesthesia (P = 0.000). However, pethidine HCL use was not statistically significantly different between spinal and epidural anesthesia. In the elective category, paracetamol was requested more after spinal than epidural or general anesthesia, P = 0.000. No significant difference was seen between epidural and general anesthesia, P = 1.000. No statistically significant difference was found among the anesthetic types in both categories regarding tramadol HCL. Length of hospital stay, ...